2020
DOI: 10.20944/preprints202007.0147.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of a Moderately Hypocaloric Mediterranean Diet on the Gut Microbiota Composition of Italian Obese Patients

Abstract: Although it is known that the gut microbiota (GM) can be modulated by diet, the efficacy of specific dietary interventions in determining its composition and diversity in obese patients remains to be ascertained. The present work aims to evaluate the impact of a moderately hypocaloric Mediterranean diet on the GM of obese and overweight patients (OB). The GM of 23 OB patients (F/M= 20/3) was compared before (T0) and after 3 months (T3) of the nutritional intervention (NI). Fecal samples were analyzed b… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 44 publications
0
4
0
1
Order By: Relevance
“…In the study of Fernandez et al, a sample of HS patients was asked, by means of an anonymous questionnaire, to indicate foods that respectively exacerbated or alleviated HS symptoms; among the former, were indicated sweets, carbohydrates, dairy and high-fat foods, while among the latter, were indicated vegetables and fruits, chicken and fish 39 . Mediterranean Diet, characterized by a high intake of vegetables, fruit, legumes, wholegrains and fish, and by a low intake of meat and dairy, is considered one of the healthiest nutritional models, and due to its richness in antioxidants compounds, such as polyphenols, contained in plant-derived food, it has considered to have a protective role against both inflammation and obesity, as well as to modulate the gut microbiota composition in obese patients 40,41,42 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the study of Fernandez et al, a sample of HS patients was asked, by means of an anonymous questionnaire, to indicate foods that respectively exacerbated or alleviated HS symptoms; among the former, were indicated sweets, carbohydrates, dairy and high-fat foods, while among the latter, were indicated vegetables and fruits, chicken and fish 39 . Mediterranean Diet, characterized by a high intake of vegetables, fruit, legumes, wholegrains and fish, and by a low intake of meat and dairy, is considered one of the healthiest nutritional models, and due to its richness in antioxidants compounds, such as polyphenols, contained in plant-derived food, it has considered to have a protective role against both inflammation and obesity, as well as to modulate the gut microbiota composition in obese patients 40,41,42 .…”
Section: Discussionmentioning
confidence: 99%
“…39 Mediterranean diet, characterized by a high intake of vegetables, fruit, legumes, wholegrains and fish, and by a low intake of meat and dairy, is considered one of the healthiest nutritional models, and due to its richness in antioxidants compounds, such as polyphenols, contained in plant-derived food, it has considered to have a protective role against both inflammation and obesity, as well as to modulate the gut microbiota composition in obese patients. [40][41][42] In HS patients, a low adherence to the Mediterranean diet has been observed, and in detail, a nutritional pattern characterized by an excess of simple carbohydrates and saturated fats, and a low intake of complex carbohydrates, fiber, mono-unsaturated and n-3 poly-unsaturated fats has been described. Moreover, in the same study, the degree of adherence to Mediterranean diet, has been shown to be negatively associated to the severity of HS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Daily intake of MedDiet changes the gut microbiota to an increased presence of Bacteroidetes, depletion of Firmicutes, lower ratio of Firmicutes/Bacteroidetes, decreased Escherichia coli (E.coli), an increased proportion of Bifidobacteria/E. coli and an increase in Proteobacteria [57][58][59]. Besides cardiovascular, metabolic, and anti-cancer benefits, MedDiet can reduce gut inflammation, lower the risk of depression, decrease the incidence of Parkinson's disease (PD) and Alzheimer's disease (AD) [60,61].…”
Section: Food and Brain-gut Axismentioning
confidence: 99%
“…Ejtahed et al2019 (27) trouxe dados sobre aumento de BCAAs e AAAs em obesos, relação do glutamato com obesidade e resistência à insulina em crianças de idade escolar e adultos de meia idade, comparados com controle. Um artigo de Pisanu et al, 2020(28)…”
unclassified